Money makes you reveal more: consequences of monetary cues on preferential disclosure of personal information - Mukherjee, Sumitava; Manjaly, Jaison A.; Nargundkar, Maithilee (Frontiers in Psychology, 2013)
With continuous growth in information aggregation and dissemination, studies on privacy preferences are important to understand what makes people reveal information about them. Previous studies have demonstrated that short-term gains and possible monetary rewards make people risk disclosing information. Given the malleability of privacy preferences and the ubiquitous monetary cues in daily lives, we measured the contextual effect of reminding people about money on their privacy disclosure preferences. In experiment 1, we found that priming money increased willingness to disclose their personal information that could be shared with an online shopping website. Beyond stated willingness, experiment 2 tested whether priming money increases propensity for actually giving out personal information. Across both experiments, we found that priming money increases both the reported willingness and the actual disclosure of personal information. Our results imply that not only do short-term rewards make people trade-off personal security and privacy, but also mere exposure to money increases self-disclosure.